KOMBINASI MINYAK IKAN LEMURU DAN MINYAK KELAPA SAWIT DALAM RANSUM TERHADAP PERFORMA DAN ORGAN DALAM AYAM BROILER: THE COMBINATION OF LEMURU FISH OIL AND PALM OIL IN THE RATION ON THE PERFORMANCE AND INTERNAL ORGANS OF BROILER CHICKENS (Jurnal Peternakan Nusantara, 2022)
The aim of this research was to evaluate the use of lemuru fish oil as palm oil substitution in ration on broiler performance. This research used 200 Ross broilers day old chick (DOC) is divided into 4 treatments and 5 replications. This research used a completely randomized design (CRD), where the treatments level of palm oil and lemuru fish oil were respectively P0 = rations containing 3% palm oil and 0% lemuru fish oil, P1 = rations containing 2% palm oil and 1% lemuru fish oil, P2 = rations containing 1% palm oil and 2% lemuru fish oil, P3 = rations containing 0% palm oil and 3% lemuru fish oil. The variables observed were feed intake, final body weight, body weight gain, feed conversion ratio (FCR), mortality, and income over feed and chick cost (IOFCC). The data were analyzed using analysis of variance (ANOVA). The significant result (P<0,05) were followed by Duncan test. The results showed a significant effect (P<0.05) in decreasing FCR in the starter period with a higher level of use of lemuru fish oil, increasing body weight gain and decreasing FCR in the finisher period with a lower level of use of lemuru fish oil, but the treatments did not significantly effect on performance broiler during the age of 35 days. Weight and percentage of internal organs and digestive tract under normal conditions, except liver weight. The conclusion of this study was the use of 3% lemuru fish oil can improve FCR in the starter phase, but the different level of palm oil and lemuru fish oil until 3 % in broiler rations does not affect on broiler performance during the age of 35 days.